Imagineering anatomy assessment amidst COVID-19: turning obstacles into achievements - Hadie, Siti Nurma Hanim; Abd Ghafar, Norzana; Abd Ghafar, Norzana; Mohd Noor, Nor Farid; Zamli, Zaitunnatakhin; Abas, Razif (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
A well-designed assessment has beneficial impacts on students’ learning and competency attainment. Failure in obtaining psychomotor learning competency, lack of understanding of assessment principles among instructors, unoptimized information and technology facilities, and difficulties in ensuring the integrity of online examination are among the threats to validity of online anatomy assessment during the COVID-19 pandemic. To ensure the validity of anatomy assessment during the pandemic, it is important to adopt several educational principles into the assessment design. We solidify the input discussed in the Malaysian Anatomical Association webinar 2021, on the challenges of anatomy online assessment and proposed six solutions to the challenges, namely adopting the programmatic assessment design, conducting small group in-person high stake examination, modifying assessment policy, utilizing question bank software, upgrading ICT facilities, and offering the ICT training to the students and instructors. It is envisioned that anatomy assessment are future ready are adaptive to change.